Strategi Kepala Sekolah dalam Mengatasi Konflik Pelayanan Administrasi di SMA Negeri 3 Unggulan Kayuagung (Al-Ilmiya: Jurnal Pendidikan Islam, 2026)
This study aims to describe the strategies used by the principal to resolve administrative service conflicts at SMA Negeri 3 Unggulan Kayuagung. Administrative service conflicts are one of the issues that can affect working relationships among staff, reduce the effectiveness of school services, and hinder the smooth running of educational activities if not properly addressed. Therefore, the principal plays a crucial role in implementing conflict management strategies to ensure a harmonious work environment and optimal administrative service delivery. This study employs a qualitative approach using a descriptive method to gain an in-depth understanding of the principal’s strategies for resolving administrative service conflicts at the school. Data collection techniques include observation, interviews, and documentation. The research subjects consist of the principal, the head of administration, administrative staff, and teachers who are considered to have direct knowledge of the implementation of administrative services at the school.This study employs Kenneth W. Thomas and Ralph H. Kilmann’s conflict management theory, which encompasses five strategies: competing, collaborating, compromising, avoiding, and accommodating. The results indicate that the school principal has implemented all five strategies in accordance with the nature of conflicts occurring within the school environment. The application of conflict management strategies helps improve communication, maintain working relationships among staff, enhance administrative staff discipline, and support the creation of more orderly, effective, and conducive administrative services at SMA Negeri 3 Unggulan Kayuagung.